Returns to investors in stocks in new industries - Gerald P. Dwyer; Cora Barnhart (Federal Reserve Bank of Atlanta, 2008)
We examine the returns to investors in publicly traded stock in new industries. We examine data from the United States on sellers of own-brand personal computers, airlines and airplane manufacturers, automobile manufacturers, railroads, and telegraphs. We find that a relatively small number of companies generate outstanding returns and many firms fail. Firms in new industries typically have high volatility of individual stocks' returns. Compared with indexes for the same period, expected returns of firms are higher for two industries, lower for one industry and roughly the same for two industries. Portfolios of firms in new industries generally have lower Sharpe ratios than the overall market.
Keywords: G1; G12; N2; N21; N22; 330; expected returns; options; lottery tickets; returns by industry